2006
DOI: 10.1515/jpm.2006.040
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective diagnosis of hypoxic myocardial injury in premature newborns

Abstract: cTnT and CK-MB levels are strong indicators of myocardial injury due to perinatal hypoxia. The cTnT level was most strongly related to RDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
2
16
0
3
Order By: Relevance
“…Cardiac involvement associated with hypoxia in newborns occur in about 29% of asphyxiated infants (MartinAncel et al, 1995). Many studies indicated that infants with perinatal asphyxia and RDS develop myocardial damage (Tapia-Rombo et al, 2000;Trevisanuto et al, 2000a,b;Szymankiewicz et al, 2006). Unfortunately, there is no information about myocardial damage associated with hypoxia in premature calves with RDS.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac involvement associated with hypoxia in newborns occur in about 29% of asphyxiated infants (MartinAncel et al, 1995). Many studies indicated that infants with perinatal asphyxia and RDS develop myocardial damage (Tapia-Rombo et al, 2000;Trevisanuto et al, 2000a,b;Szymankiewicz et al, 2006). Unfortunately, there is no information about myocardial damage associated with hypoxia in premature calves with RDS.…”
Section: Discussionmentioning
confidence: 99%
“…This parameter is often depressed after birth asphyxia and is a useful marker of severity and a prognostic indicator in asphyxia (16). In addition, troponin T, a marker of cardiac injury, was measured (1,17). To assess activation or suppression of mitochondrial apoptotic and survival pathways in myocardial left ventricular tissue, the protein level of apoptosis executioner cysteinyl aspartate-specific protease-3 (caspase-3) was determined.…”
Section: Articles Seehase Et Almentioning
confidence: 99%
“…ulti-organ dysfunction is a common outcome of severe perinatal asphyxia (1,2). One of the organs significantly involved in the fate of the asphyctic newborn is the heart (3,4); it can compromise the oxygen supply of other organs, resulting in irreversible injury (5).…”
mentioning
confidence: 99%
“…renatal asphyxia can affect all organs due to poor perfusion and reduced oxygen delivery, but the most detrimental effects are observed in the central nervous and cardiovascular system (1)(2)(3)(4)(5). Therefore, it is not surprising that asphyxia is the third major cause of neonatal mortality and accounts for more than one million neonatal deaths worldwide per year (6).…”
mentioning
confidence: 99%